Dry matter yield and production costs in grazing systems on dairy farms of Costa Rica - Villalobos, Luis (2013)
Biomass production costs and dry matterkilogram cost were evaluated in kikuyu grass (Kikuyuocloa clandestina), perennial ryegrass (Lolium perenne) and African stargrass (Cynodon nlemfuensis), along one year, in 8 dairy farms located in Cartago (2), San José (2) and Alajuela (4) provinces. Average dry matter yield per cycle was 3395 kg.ha-1 DM for the three grasses. Annual yield is influenced by the regrowth period of each species, with values of 40 170, 38 731 and 28 995 kg.ha-1 DM for African stargrass, kikuyu grass and perennial ryegrass, respectively. Biomass production varies during the year, and the utilization by cattle has a less utilization of these fields during the months of highest yield. Since the stocking rate, the occupational period and the grazing area are not adjusted an the basis of dry matter availability, dairy cattle has a lower utilization rate in the paddocks. Average costs for labor, agricultural inputs and land were (in Costa Rican currency) 72.433, 505.515 and 18.760 colones.ha-1, respectively. Inputs had the highest impact in the costs structure in grazing dairy farms. Costs for dry matter kilogram produced and consumed were 16.6 and 44.4 colones, respectively, for all 3 pastures; the cost of dry matter-kilogram consumed was affected by the rate of utilization in the grazing paddocks. Dairy farms with higher investment in pastures had a higher return in kg.ha-1 milk as well.